2021
DOI: 10.1002/lary.29582
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Interpret Pediatric Vocal Fold Mobility: A Laryngeal Ultrasound Training Module

Abstract: Objectives/Hypothesis Vocal fold movement impairment (VFMI) in infants and children is most commonly evaluated by flexible nasolaryngoscopy (FNL). FNL in this population can be challenging due to movement, floppy supraglottic structures, or secretions. Laryngeal ultrasound (LUS) may be an alternative, less invasive means of evaluating VFMI that also decreases aerosolization during the COVID‐19 pandemic. The primary objective was to examine LUS interpretation proficiency for VFMI via an educational module. A se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Similarly, laryngoscopy combined with LUS is likely to clarify a diagnosis of suspected VFI compared to a single investigation. LUS has also been shown to be easy to learn for clinicians other than otolaryngologists (15,16,(19)(20)(21)(22), suggesting it may be a useful tool in remote areas where an otolaryngologist may not be available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, laryngoscopy combined with LUS is likely to clarify a diagnosis of suspected VFI compared to a single investigation. LUS has also been shown to be easy to learn for clinicians other than otolaryngologists (15,16,(19)(20)(21)(22), suggesting it may be a useful tool in remote areas where an otolaryngologist may not be available.…”
Section: Discussionmentioning
confidence: 99%
“…Our radiologists report LUS in a qualitative fashion, i.e., they report whether mobility is normal, reduced, or absent. Few studies have described quantitative measures such as maximum glottic angle and vocal fold-arytenoid angle to aid the interpretation of LUS (22,23). These authors concluded that the accuracy of LUS increases by using quantitative measures.…”
Section: Discussionmentioning
confidence: 99%
“…It may be a diagnostic alternative for the evaluation of laryngeal disorders, well tolerated by patients and parents and easy to perform. It also decreases aerosolization during COVID-19 pandemic and may serve as an alternative tool of visualizing the larynx in children who can not tolerate laryngoscopy [ 24 ]. During TLUGS patients are scanned with a linear probe, in the supine position, with the neck well extended.…”
Section: Discussionmentioning
confidence: 99%
“…No sedation or anesthesia is required [ 25 ]. Many authors have demonstrated that laryngeal ultrasound can be used to evaluate vocal cord function, allowing early detection of vocal fold paralysis in children [ 24 , 26 , 27 ]. The diagnostic criteria for vocal fold paralysis using TLUGS are: abnormal mobility, hyperechoic air-column band of the glottic rima during phonation, flaccid vocal fold and asymmetry of the glottal structures [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation